2012
DOI: 10.1902/jop.2011.110548
|View full text |Cite
|
Sign up to set email alerts
|

Serum Plasminogen Activator Inhibitor‐1 and Tumor Necrosis Factor‐α Levels in Obesity and Periodontal Disease

Abstract: Serum PAI-1 levels may play an important role in the association between periodontal disease and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Platelets release TGF‐beta as a latent growth factor, requiring activation by factors such as thrombospondin‐1 and plasmin . Serum contains factors that control the activity of these enzymes, such as plasminogen activator inhibitor‐1 and factors that bind TGF‐beta . Involving these mechanisms, serum might inhibit the activation of TGF‐beta that is directly released by platelets.…”
Section: Discussionmentioning
confidence: 95%
“…Platelets release TGF‐beta as a latent growth factor, requiring activation by factors such as thrombospondin‐1 and plasmin . Serum contains factors that control the activity of these enzymes, such as plasminogen activator inhibitor‐1 and factors that bind TGF‐beta . Involving these mechanisms, serum might inhibit the activation of TGF‐beta that is directly released by platelets.…”
Section: Discussionmentioning
confidence: 95%
“…Both Bizzarro et al . and Akman et al . documented the importance of serum PAI‐1 as a marker in periodontal disease, with PAI‐1 levels increasing with increases in inflammation and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of periodontitis increases, there is a greater systemic inflammatory response . Previous studies showed that periodontitis leads to atherosclerosis through periodontal pathogens and their by‐products, or through the release of inflammatory mediators from periodontal tissue that induce endothelial dysfunction . Pathological studies of atherosclerotic plaques have identified the presence of periodontal pathogens …”
Section: Introductionmentioning
confidence: 99%